2003
DOI: 10.1016/j.cub.2003.11.021
|View full text |Cite
|
Sign up to set email alerts
|

PLD1 Regulates mTOR Signaling and Mediates Cdc42 Activation of S6K1

Abstract: Our observations reveal the involvement of PLD1 in mTOR signaling and cell size control, and provide a molecular mechanism for Cdc42 activation of S6K1. A new cascade is proposed to connect mitogenic signals to mTOR through Cdc42, PLD1, and PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
140
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(153 citation statements)
references
References 42 publications
8
140
1
1
Order By: Relevance
“…A recent study showed that mTOR activation by mechanical stimulation of skeletal muscle involved phospholipase D producing the lipid messenger phosphatidic acid (PA) . PA binds the FRB domain of TOR and activates S6K1 activity (Fang et al, 2003). S6K activity is also regulated by other exercise-induced stress conditions such as cyclic strain imposed on smooth muscle cells (SMC).…”
Section: Ultraviolet and Rosmentioning
confidence: 99%
“…A recent study showed that mTOR activation by mechanical stimulation of skeletal muscle involved phospholipase D producing the lipid messenger phosphatidic acid (PA) . PA binds the FRB domain of TOR and activates S6K1 activity (Fang et al, 2003). S6K activity is also regulated by other exercise-induced stress conditions such as cyclic strain imposed on smooth muscle cells (SMC).…”
Section: Ultraviolet and Rosmentioning
confidence: 99%
“…25,[31][32][33] Overexpression of either PLD1 or PLD2 activates mTORC1 signaling in various types of cells (reviewed in ref. 34), whereas PLD knockdown blocks mitogenic activation of mTORC1 signaling.…”
Section: Phosphatidic Acid and Phospholipase D In Mtorc1 Signalingmentioning
confidence: 99%
“…34), whereas PLD knockdown blocks mitogenic activation of mTORC1 signaling. 32,35,36 The small G protein Cdc42 had long been known as an activator of S6K1 with an exact mechanism yet to be determined, 37 and now PLD1 has been revealed as a molecular link between Cdc42 and mTORC1. 32 In addition to PLD, two other PA-producing enzymes-lysophosphatidic acid acyltransferase (LPAAT) and diacylglycerol kinase (DGK)-have also been shown to regulate mTOR signaling through PA, 38,39 further validating the link between PA and mTOR.…”
Section: Phosphatidic Acid and Phospholipase D In Mtorc1 Signalingmentioning
confidence: 99%
“…PLD plays a role in growth factor-induced cellular proliferation [3][4][5][6] and facilitates oncogenic transformation [7][8][9][10]. Endogenous PLD activity is significantly increased in several types of cancers [11][12][13][14][15], as well as in cell lines transformed with oncogenes [4,5,8,10,[16][17][18][19]. PLD may participate in the activation of p42/44 ERK via Raf-1 translocation to the plasma membrane [20][21][22][23], as well as in the survival signaling mediated by PI3K/AKT activation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Bad, caspase 9, Mdm2) [29][30][31][32]. Interestingly, most of these effectors can also be regulated by PLD [16,21,22,25,[33][34][35][36]. Furthermore, AKT and bacterial PLD interact [37] and PLD plays a critical role in the PI3K-dependent activation of AKT [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%